Edukasi Isi Piringku untuk Meningkatkan Pola Makan Sehat pada Siswa Sekolah Dasar - Fatma Syukrina; Rizki Rahma Wati (STAI Darul Qalam Tangerang, 2025)
A healthy diet among elementary school-aged children is crucial for optimal growth and development, as well as for preventing nutritional problems such as obesity and stunting. This study aims to improve elementary school students’ knowledge and healthy eating behaviors through the “My Plate” education program. The method used was a community service program employing an educational intervention approach that included short lectures, “My Plate” visualizations, healthy plate arrangement practice, educational games, educational posters, and interactive quizzes. Participants were elementary school students aged 7–12 years. Results showed a significant increase in students’ nutritional knowledge following the education, as well as positive changes in eating behaviors, such as beginning to choose fruits and vegetables. Teacher involvement, parental support, and student interest were key factors in the program’s success. This program is effective in raising awareness about the importance of balanced nutrition and fostering healthy eating habits from an early age. In conclusion, the “My Plate” education program effectively improves elementary school students’ knowledge and healthy eating behaviors, with interactive and participatory methods proven successful in building healthy eating habits